2017
DOI: 10.1063/1.4976574
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of Seebeck coefficients in a magnetic semiconductor CuFeS2

Abstract: We analyze the Seebeck coefficients of a magnetic semiconductor CuFeS2 using first-principles calculation methods based on density functional theory. The calculated temperature dependence of the Seebeck coefficient in the antiferromagnetic phase reproduces a distinctive behavior in a bulk CuFeS2, such as a peak structure at a low temperature and weak temperature dependence around room temperature. In doped systems, almost linear temperature dependence appears. Despite not including any effect beyond the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 35 publications
4
19
0
1
Order By: Relevance
“…However, to achieve an effective, deployable on-chip thermoelectric energy harvester 3 , materials with a large thermoelectric power, i.e., Seebeck coefficient, are key. Spin caloritronics [4][5][6][7][8] is an interdisciplinary field which merges spintronics [9][10][11] with thermoelectrics [12][13][14][15][16][17][18][19] and has attracted tremendous attentions lately. A key device within spintronics and the IoT, and thus an attractive target to consider for spin caloritronics, is the magnetic tunnel junction (MTJ) [20][21][22][23] .…”
mentioning
confidence: 99%
“…However, to achieve an effective, deployable on-chip thermoelectric energy harvester 3 , materials with a large thermoelectric power, i.e., Seebeck coefficient, are key. Spin caloritronics [4][5][6][7][8] is an interdisciplinary field which merges spintronics [9][10][11] with thermoelectrics [12][13][14][15][16][17][18][19] and has attracted tremendous attentions lately. A key device within spintronics and the IoT, and thus an attractive target to consider for spin caloritronics, is the magnetic tunnel junction (MTJ) [20][21][22][23] .…”
mentioning
confidence: 99%
“…Taking into account that both observed T min are well below the Θ D = 263 K, reported for CuFeS 2 , such an assumption would be justified. As shown by the first principles calculations of CuFeS 2 , where the phonon drag effect is not included, features of the temperature dependence of the Seebeck coefficient appear to be able to be explained by the particular electronic structure of CuFeS 2 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the improvement of thermoelectric performance of chalcopyrite doped with Mn, Co, and Ni can be of magnetic origin, however, this point has not been clarified yet. First principles calculations of CuFeS 2 showed the stability of the antiferromagnetic state and reproduced relatively large Seebeck coefficients and particular temperature dependences of pristine and doped chalcopyrite . However, a gap in the absolute magnitude of the Seebeck coefficients indicated that there may be magnetic effects at play not included in the calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic phase can significantly affect the electronic properties, such as effective mass, band gap, and density of states (DOS) near the Fermi level. However, substantial computations for magnetic systems usually either are assumed in a ferromagnetic order or a non‐spin‐polarized description of electron subsystem is enforced . These ways simplify the electron spin order to reduce computational cost, however, it is obviously inaccurate to describe the spin‐disordered (paramagnetic) system .…”
mentioning
confidence: 99%
“…However, substantial computations for magnetic systems usually either are assumed in a ferromagnetic order or a non‐spin‐polarized description of electron subsystem is enforced . These ways simplify the electron spin order to reduce computational cost, however, it is obviously inaccurate to describe the spin‐disordered (paramagnetic) system . If non‐spin‐polarized description of electron subsystem is employed for magnetic system, the electronic properties of system would severely deviate from the truth.…”
mentioning
confidence: 99%